Correlation of Single Breath Count Test with Peak Expiratory Flow Rate in Adult Patients Post COVID-19 Infection - Marcherly Wardi; Siti Chandra Widjanantie; Heidy Agustin; Cleopas Martin Rumende; Andari Perwira Putri; Sri Wahyudati (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: The utilization of spirometry has garnered significant attention recently due to its potential role in transmitting COVID-19. There is a critical need for a straightforward bedside assessment capable of accurately measuring respiratory function without relying on equipment and minimizing the risk of airborne transmission. AIMS: To know the correlation between Single Breath Count Test (SBCT) values and Peak Expiratory Flow Rate (PEFR) values in adult patients recovering from COVID-19. METHOD: This study presents a cross-sectional design with consecutive subject recruitment. The SBCT was administered using a metronome, while PEFR was measured using a Mini Wright Peak Flow Meter on a sample of 38 participants, comprising 18 men and 20 women. RESULT: Statistical analysis using Pearson’s parametric correlation test revealed a significant relationship between SBCT and PEFR (p < 0.05), with a moderate positive correlation observed (r = 0.516). CONCLUSION: This research demonstrates a significant, moderate positive correlation between SBCT and PEFR in adult post-COVID-19 patients, indicating that higher SBCT values correspond to higher PEFR measurements.